Implementation of Discovery Learning Models to Improve Understanding of Soci-Cultural Change Material at SMP Negeri 02 Rumbia, Indonesia - Arisland, Arisland (Journal of Teaching and Education, 2023)
This study aimed to improve students’ understanding of socio-cultural change in class IX at SMP Negeri 02 Rumbia through the implementation of the Discovery Learning model. The research was conducted using Classroom Action Research (CAR) over three cycles, each consisting of planning, action, observation, and reflection. The participants were class IX students, and data were collected from both students and teachers through observation and written tests, then analyzed qualitatively using descriptive analysis. The findings showed that students’ understanding gradually improved across the cycles. In Cycle I, the average learning outcome was 72.22 with 61% of students achieving mastery. Cycle II showed an increase to an average score of 79.17 with 75% mastery, and in Cycle III, the average score reached 89.72 with 100% of students achieving mastery, categorized as “Very Good.” These results indicate that the Discovery Learning model effectively enhances students’ comprehension of socio-cultural change, fostering active engagement, critical thinking, and collaborative learning.